The era of Migratory Entrapment: African Migration towards Mexico's Northern Border - Odgers-Ortiz, Olga (2024)
In his classic book "Beyond the Line" (1994), Durand identifies six eras or stages in the history of Mexico/US migration, showing that in 130 years of migratory history there have been both continuities and important ruptures. In this article we argue that, due to the transformations that have occurred in the Mexican migration scenario, we find ourselves in a new stage, which we could call "the era of entrapment". In the following pages, we begin by discussing the concept of "migratory entrapment"; in the second section we point out the key processes and moments in the shaping of the era of entrapment; the third section illustrates the dynamics of entrapment based on the case of the population originating in Africa. Finally, we conclude by arguing that migratory entrapment, as observed at Mexico's northern border, is only a local expression of a global phenomenon.